Determinants of Economic Growth in Central Java - Dimas Ruhen; Diah Setyorini Gunawan (EKO-REGIONAL, 2018)
Central Java Province is one of the province in Java Island which has potential natural resources and human resources , but current Central Java economic growth is still far from other provinces on Java island. With the abudance of resources in Central Java the province and still low Growth Economics, this study analyze the effects of foreign investment, labor, and human capital investment, to the economic growth in ten regencies / city of Central Java Province. The analysis method in this study is using the panel data method with some criteria in the panel data, then the best model is the fixed effect or Least Square Dummy Variable (LSDV). The result of the research are: (1) Foreign investment has positive and insignificant effect, (2) the workforce has positive and significant influence, (3) human capital investment has positive and significant influence, (4) Semarang regency becomes the most economic growth area High compared with ten other districts / cities. The implications of this research are first, in increase the economic growth of ten regencies / cities in Central Java Province, the local government should create a conducive investment climate and simplify the investment licensing process so it will increase domestic and foreign investment and encourage economic growth. Second, the government's labor skill training can be an alternative for unskilled workers. Third, local governments can provide budget allocations for education and health so that the capital which portrayed by workers quality can deliver positive results.Keywords: Economic Growth, Foreign Direct Investment (FDI), Labora, and Human Capital Investment.